Kinematics of formation of the western and central parts of the Ukrainian shield between 2,02—2,05 Ga ago - S.V. Mychak (Геофизический журнал, 2015)
On the basis of study of Umansk, Novograd-Voolynsk and Novoukrainsk granitoid massif of western and central parts of the Ukrainian shield by tectonophysical methods intensely deformed state of the earth's crust in the period between 2,02—2,05 Ga has been revealed. The single paleofield of tectonic stress for Nemirovsk and Lelekovsk stages has been restored. A refined scale of deformation stages of the north-western and central part of the Ukrainian Shield in the time interval 2,45—1,73 Ga has been composed. The idea of counter-clockwise turning the western part of the shield relative to its central part during the interval of 2,02—2,05 Ga is being substantiated.